Treatment of drug addiction and psychopathology: A field study - Antonio Souto; Luis Fernandez-Rios; Manuel Isorna (European Journal of Psychology Applied to Legal Context, 2010)
Field study to assess the concurrence of the psychopathology of drug addiction, and to evaluate the efficacy of pharmacological treatment versus drug-free treatments for the psychopathology of drug addiction. A total of 261 patients treated for drug addiction, 131 on a drug-free treatment and the remaining 130 patients received a drug regime, of which 113 were, according to the Prochaska and Decrement’s Transtheorical Model, in a initial phase of the treatment (from 15 days to 6 months of treatment) and 148 in a maintenance phase in drug treatment (> 6 months), were psychopathologically assessed using the SCL-90-R (Derogatis, 2002). A field study with a 2 X 2 design (treatment: drug-free vs. drug-regime) and (treatment phase: initial phase vs. maintenance in drug treatment) was carried out. The results support the hypothesis of a dual diagnosis, that is, the comorbidity of psychopathology and drug addiction. On the whole, treatment for drug addiction had a significant impact on reducing associated psychopathology. Finally, the results are discussed in the light of the implications for the treatment of drug addiction.